Analysis of Mathematics Problem Solving Ability Based on The Learning Style Class VIII At SMPN 13 Mataram - Sudi Prayitno; Nurul Hikmah; Agustina, Sindi Nopita (Indonesian Journal of STEM Education, 2020)
The ability to solved problems is an important element in learning mathematics. But in reality at SMPN 13 Mataram this ability still low with a percentage of 70% of students having low problem solving abilities. The reason is teachers tend use same learning methods and students also not know how to optimize their own potential in learning. One way to make learning mathematics effective is by knowing learning styles used by students. This study aims to describe the problem-solving abilities claass VIII at SMPN 13 Mataram based on learning styles. The type of research used is qualitative research with research instruments namely problem solving ability tests, learning style questionnaires and interviews. The results obtained from 28 students were students with 12 students in the visual style category, 15 auditory students and 1 student with a kinetic learning style. The conclusion from the research results is that from the four stages of problem solving based on the theory of polya. , The visual learning style is able to complete the four stages very well. Auditory learning styles can only complete the 3 stages well and do not do the re-checking stage. In the kinetic learning style, it can only solve one problem and does not carry out the rechecking stage. The main difference between these three learning styles is the accuracy in problem processing. Keywords: problem solving ability, learning style, SMPN 13 Mataram ABSTRAK ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DITINJAU DARI GAYA BELAJAR SISWA KELAS VIII SMPN 13 MATARAM Kemampuan pemecahan masalah menjadi salah satu elemen penting dalam pembelajaran matematika. Namun kenyataannya di SMPN 13 Mataram kemampuan tersebut masih rendah dengan persentase 70% siswa memiliki kemampuan pemecahan masalah yang rendah. Salah satu cara mengoptimalkan pembelajaran matematika dengan mengetahui gaya belajar yang digunakan siswa. Penelitian ini bertujuan untuk mendeskripsikan kemampuan pemecahan masalah di SMPN 13 Mataram kelas VIII ditinjau dari gaya belajar. Jenis penelitian yang digunakan yaitu penelitian kualitatif dengan instrumen penelitian yaitu tes kemampuan pemecahan masalah, angket gaya belajar dan wawancara. Hasil yang didapatkan dari 28 siswa terdapat siswa dengan 12 siswa kategori gaya visual, 15 siswa auditori dan 1 siswa dengan gaya belajar kinetik. Kesimpulan dari hasil penelitian yaitu dari empat tahapan pemecahan masalah berdasarkan teori polya, gaya belajar visual mampu menyelesaikan empat tahapan dengan sangat baik. Gaya belajar auditori hanya dapat menyelesaikan 3 tahapan dengan baik dan tidak melakukan tahapan memeriksa kembali. Pada gaya belajar kinetik hanya dapat menyelesaikan satu masalah dan tidak melakukan tahapan memeriksa kembali. Perbedaan utama dari ketiga gaya belajar ini yaitu ketelitian pada pengerjaan soal. Kata kunci: kemampuan pemecahan masalah, gaya belajar, SMPN 13 Mataram